Macrodomain structure formed in (Sr0.7Bi0.2□0.1)TiO3-modified Bi0.5Na0.4 K0.1TiO3 thin film. Issue 19 (1st October 2021) - Xu, Liuxue; Ni, Feier; Zhu, Kun; Song, Baijie; Liu, Yang; Yan, Hao; Shen, Bo; Zhai, Jiwei
Abstract: The performance of piezoelectric materials can often be improved near the morphotropic phase boundary (MPB), in this work, we introduced (Sr0.7 Bi0.2 □0.1 )TiO3 into Bi0.5 Na0.4 K0 · 1 TiO3 thin films to regulate their properties. (1- x )BNKT– x SBT ( x  = 0.05, 0.10, 0.20, 0.30) lead free piezoelectric thin films were deposited on Pt(111)/Ti/SiO2 /Si substrates by the sol–gel method, which was designed by the principle of optimal tolerance factor. The XRD and Raman spectra were investigated in detail to prove the formation of MPB in BNKT–0.10SBT thin films, and the most direct evidence is the movement of T F-R near room temperature. The rarest is the formation of macrodomain structure at MPB, which is especially beneficial to the improvement of piezoelectric property. There is no doubt that the most excellent ferroelectric ( P m  = 59 μC cm −2, P r  = 13 μC cm −2 @700 kV/cm) and piezoelectric properties (72% higher than the initial component) can be obtained from the BNKT–0.10SBT thin film. The MPB formed when tolerance factor was adjusted to 0.9816, meanwhile macrodomain structure was observed under electric field, so that the ferroelectric and piezoelectric properties have been significantly improved at this point. This study provides a useful guide to research MPB in BNT-based thin films in order to improve ferroelectric and piezoelectric performances.